Scanning Capacitance Microscopy in the Quantum Hall Regime - Suddards, Matthew Edmund (2007)
This thesis discusses the development of a novel scanning capacitance microscope (SCM) that enables the investigation of the local capacitance and conductivity of surfaces and near-surface nanostructures at cryogenic temperatures and high magnetic fields.